The Speed Calculating Increasing Method of the Markov Model Network Node - Pustovoitov, Pavlo; Okhrimenko, Maxim; Voronets, Vitalii; Udalov, Dmitry (Національний технічний університет "Харківський політехнічний інститут", 2021)
The subject of this research is the image classification methods based on a set of key points descriptors. The goal is to increase the performance of classification methods, in particular, to improve the time characteristics of classification by introducing hashing tools for reference data representation. Methods used: ORB detector and descriptors, data hashing tools, search methods in data arrays, metrics-based apparatus for determining the relevance of vectors, software modeling. The obtained results: developed an effective method of image classification based on the introduction of high-speed search using hash structures, which speeds up the calculation dozens of times; the classification time for the considered experimental descriptions increases linearly with decreasing number of hashes; the minimum metric value limit choice on setting the class for object descriptors significantly affects the accuracy of classification; the choice of such limit can be optimized for fixed samples databases; the experimentally achieved accuracy of classification indicates the efficiency of the proposed method based on data hashing. The practical significance of the work is - the classification model’s synthesis in the hash data representations space, efficiency proof of the proposed classifiers modifications on image examples, development of applied software models implementing the proposed classification methods in computer vision systems.

Предметом досліджень є методи класифікації зображень за множиною дескрипторів ключових точок. Метою є підвищення продуктивності методів класифікації, зокрема, прискорення часових показників класифікації шляхом впровадження засобів хешування для подання еталонних даних. Методи, що застосовуються: детектор та дескриптори ORB, засоби хешування даних, методи пошуку в масивах даних, апарат визначення релевантності векторів на основі метрик, програмне моделювання. Отримані результати: розроблено ефективний метод класифікації зображень на основі впровадження швидкісного пошуку із використанням хеш-структур, що прискорює обчислення в десятки разів; час класифікації для розглянутих експериментальних описів лінійно зростає зі зменшенням числа хеш-кошиків; вибір порогу для значення мінімуму метрики при встановленні класу для дескрипторів об’єкту суттєво впливає на точність класифікації; вибір такого порогу може бути оптимізовано для фіксованих баз зразків; експериментально досягнута точність класифікації вказує на працездатність та результативність запропонованого методу на підґрунті хешуванням даних. Практична значущість роботи – побудова моделей класифікації у просторі хеш-подання даних, підтвердження працездатності запропонованих модифікацій класифікаторів на прикладах зображень, розроблення прикладних програмних моделей для впровадження запропонованих методів класифікації у системах комп’ютерного зору.
Метод підвищення швидкості модельного вузла Маркова
Keywords: computer vision; structural methods of image classification; ORB descriptor; hashing; комп’ютерний зір; структурні методи класифікації зображень; дескриптор ORB; хешування